Plastic and genomic change of a newly established lizard population following a founder event - Iva Sabolić; Óscar Mira; Débora Y. C. Brandt; Duje Lisičić; Jessica Stapley; Maria Novosolov; Robert Bakarić; Ivan Cizelj; Marko Glogoški; Tomislav Hudina; Maxime Taverne; Morten E. Allentoft; et al. (Molecular Ecology, 2024)
Understanding how phenotypic divergence arises among natural populations remains one of the major goals in evolutionary biology. As part of competitive exclusion experiment conducted in 1971, 10 individuals of Italian wall lizard ( Podarcis siculus (Rafinesque‐Schmaltz, 1810)) were transplanted from Pod Kopište Island to the nearby island of Pod Mrčaru (Adriatic Sea). Merely 35 years after the introduction, the newly established population on Pod Mrčaru Island had shifted their diet from predominantly insectivorous towards omnivorous and changed significantly in a range of morphological, behavioural, physiological and ecological characteristics. Here, we combine genomic and quantitative genetic approaches to determine the relative roles of genetic adaptation and phenotypic plasticity in driving this rapid phenotypic shift. Our results show genome‐wide genetic differentiation between ancestral and transplanted population, with weak genetic erosion on Pod Mrčaru Island. Adaptive processes following the founder event are indicated by highly differentiated genomic loci associating with ecologically relevant phenotypic traits, and/or having a putatively adaptive role across multiple lizard populations. Diverged traits related to head size and shape or bite force showed moderate heritability in a crossing experiment, but between‐population differences in these traits did not persist in a common garden environment. Our results confirm the existence of sufficient additive genetic variance for traits to evolve under selection while also demonstrating that phenotypic plasticity and/or genotype by environment interactions are the main drivers of population differentiation at this early evolutionary stage.

Two‐speed genomes of Epichloe fungal pathogens show contrasting signatures of selection between species and across populations - Artemis D. Treindl; Jessica Stapley; Daniel Croll; Adrian Leuchtmann (Molecular Ecology, 2024)
Antagonistic selection between pathogens and their hosts can drive rapid evolutionary change and leave distinct molecular footprints of past and ongoing selection in the genomes of the interacting species. Despite an increasing availability of tools able to identify signatures of selection, the genetic mechanisms underlying coevolutionary interactions and the specific genes involved are still poorly understood, especially in heterogeneous natural environments. We searched the genomes of two species of Epichloe plant pathogen for evidence of recent selection. The Epichloe genus includes highly host‐specific species that can sterilize their grass hosts. We performed selection scans using genome‐wide SNP data from seven natural populations of two co‐occurring Epichloe sibling species specialized on different hosts. We found evidence of recent (and ongoing) selective sweeps across the genome in both species. However, selective sweeps were more abundant in the species with a larger effective population size. Sweep regions often overlapped with highly polymorphic AT‐rich regions supporting the role of these genome compartments in adaptive evolution. Although most loci under selection were specific to individual populations, we could also identify several candidate genes targeted by selection in sweep regions shared among populations. The genes encoded small secreted proteins typical of fungal effectors and cell wall‐degrading enzymes. By investigating the genomic signatures of selection across multiple populations and species, this study contributes to our understanding of complex adaptive processes in natural plant pathogen systems.

The genomic basis of eco‐evolutionary dynamics - Alejandra Rodríguez‐Verdugo; James Buckley; Jessica Stapley (Molecular Ecology, 2017)
Recent recognition that ecological and evolutionary processes can operate on similar timescales has led to a rapid increase in theoretical and empirical studies on eco‐evolutionary dynamics. Progress in the fields of evolutionary biology, genomics and ecology is greatly enhancing our understanding of rapid adaptive processes, the predictability of adaptation and the genetics of ecologically important traits. However, progress in these fields has proceeded largely independently of one another. In an attempt to better integrate these fields, the centre for ‘Adaptation to a Changing Environment’ organized a conference entitled ‘The genomic basis of eco‐evolutionary change’ and brought together experts in ecological genomics and eco‐evolutionary dynamics. In this review, we use the work of the invited speakers to summarize eco‐evolutionary dynamics and discuss how they are relevant for understanding and predicting responses to contemporary environmental change. Then, we show how recent advances in genomics are contributing to our understanding of eco‐evolutionary dynamics. Finally, we highlight the gaps in our understanding of eco‐evolutionary dynamics and recommend future avenues of research in eco‐evolutionary dynamics.

Transposable elements as agents of rapid adaptation may explain the genetic paradox of invasive species - Jessica Stapley; Anna W. Santure; Stuart R. Dennis (Molecular Ecology, 2015)
Rapid adaptation of invasive species to novel habitats has puzzled evolutionary biologists for decades, especially as this often occurs in the face of limited genetic variability. Although some ecological traits common to invasive species have been identified, little is known about the possible genomic/genetic mechanisms that may underlie their success. A common scenario in many introductions is that small founder population sizes will often lead to reduced genetic diversity, but that invading populations experience large environmental perturbations, such as changes in habitat and environmental stress. Although sudden and intense stress is usually considered in a negative context, these perturbations may actually facilitate rapid adaptation by affecting genome structure, organization and function via interactions with transposable elements ( TE s), especially in populations with low genetic diversity. Stress‐induced changes in TE activity can alter gene action and can promote structural variation that may facilitate the rapid adaptation observed in new environments. We focus here on the adaptive potential of TE s in relation to invasive species and highlight their role as powerful mutational forces that can rapidly create genetic diversity. We hypothesize that activity of transposable elements can explain rapid adaptation despite low genetic variation (the genetic paradox of invasive species), and provide a framework under which this hypothesis can be tested using recently developed and emerging genomic technologies.

Influence of alternate reproductive tactics and pre- and postcopulatory sexual selection on paternity and offspring performance in a lizard - J. Scott Keogh; Kate D. L. Umbers; Eleanor Wilson; Jessica Stapley; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2013)

Genetic mapping of the major histocompatibility complex in the zebra finch (Taeniopygia guttata) - Robert Ekblom; Jessica Stapley; Alex D. Ball; Tim Birkhead; Terry Burke; Jon Slate (Immunogenetics, 2011)

Mating effort and female receptivity: how do male guppies decide when to invest in sex? - Palestina Guevara-Fiore; Jessica Stapley; Penelope J. Watt (Behavioral Ecology and Sociobiology, 2010)

Erratum to: Gene mapping in the wild with SNPs: guidelines and future directions - Jon Slate; Jake Gratten; Dario Beraldi; Jessica Stapley; Matt Hale; Josephine M. Pemberton (Genetica, 2010)

On the use of large marker panels to estimate inbreeding and relatedness: empirical and simulation studies of a pedigreed zebra finch population typed at 771 SNPs - ANNA W. SANTURE; JESSICA STAPLEY; ALEXANDER D. BALL; TIM R. BIRKHEAD; TERRY BURKE; JON SLATE (Molecular Ecology, 2010)
In recent years there has been a dramatic increase in the availability of high density genetic marker data for both model and non‐model organisms. A potential application of these data is to infer relatedness in the absence of a complete pedigree. Using a marker panel of 771 SNPs genotyped in three generations of an extensive zebra finch pedigree, correlations between pedigree relatedness and seven marker‐based estimates of relatedness were examined, as was the relationship between heterozygosity and inbreeding. Although marker‐based and pedigree relatedness were highly correlated, the variance in estimated relatedness was high. Further, the correlation between heterozygosity and inbreeding was weak, even though mean inbreeding coefficient is typical of that seen in wild vertebrate pedigrees; the weak relationship was in part due to the small variance in inbreeding in the pedigree. Our data suggest that using marker information to reconstruct the pedigree, and then calculating relatedness from the pedigree, is likely to give more accurate relatedness estimates than using marker‐based estimators directly.

Gene mapping in the wild with SNPs: guidelines and future directions - Jon Slate; Jake Gratten; Dario Beraldi; Jessica Stapley; Matt Hale; Josephine M. Pemberton (Genetica, 2009)

Do mountain log skinks ( Pseudemoia entrecasteauxii ) modify their behaviour in the presence of two predators? - Jessica Stapley (Behavioral Ecology and Sociobiology, 2004)

Ecological Example of Conditioned Flavor Aversion in Plant–Herbivore Interactions: Effect of Terpenes of Eucalyptus Leaves on Feeding by Common Ringtail and Brushtail Possums - Ivan R. Lawler; Jessica Stapley; William J. Foley; Bart M. Eschler (Journal of Chemical Ecology, 1999)